METHODOLOGY FOR PREDICTING CHEMICAL EQUILIBRIA SHIFT: CHANGING SYSTEM COMPOSITION AT CONSTANT TEMPERATURE - SOLAZ-PORTOLÉS, Joan Josep; CAURIN, Carlos (Tchê química, 2012)
The subject of perturbations of an equilibrium system and the direction in which it shifts as it moves towards a new equilibrium is an important aspect of general and physical chemistry courses. Of particular importance is students' ability to predict the effects of changing conditions on the position of chemical equilibrium. On a teaching context, the Le Chatelier's principle is still used as an infallible principle without showing its limitations which can lead to very important misconceptions. In this paper it is presented a teaching methodology to avoid the Le Chatelier’s qualitative rule. This methodology is based on extent of reaction, affinity of reaction, and thermodynamic potentials. Focusing on the effects of adding more reactants or products on chemical equilibrium (at constant temperature), our proposal gives the mathematical expression of the variation of the extent of reaction with the infinitesimal variation in the number of moles, and it allows to make exact predictions about the evolution of a perturbed chemical equilibrium system.